“Migrant Mother”: the Depression Era Madonna - Ivana Marvánová (American and British Studies Annual, 2010)
In the 1930s, the American photography has been enriched by the works of the group of documentary photographers in which Dorothea Lange seemed to play the most significant role. Lange’s portrait of a woman holding a baby and being surrounded by two of her other children, called the Migrant Mother, immediately exceeded boundaries of common picture and became more than an icon of one unhappy decade. The photograph’s unusual composition and Lange’s ability to catch inconveniences such as sorrow, destitution, or starvation on the one side, together with hope, confidence, and solidarity on the other side, forced many art critics to analyze the photograph and discuss its hidden meanings. One of such image’s explanations compares it to the portrayal of Virgin Mary holding baby Jesus. The article tries to explain this biblical interpretation, as well as to introduce into the story of a creation of one of the best known photograph of the twentieth century.